Implementation of the Pancasila Student Profile Strengthening Project in Elementary Schools in Bandar Lampung City - Lestari, Yulita Dwi; Juwantara, Ridho Agung; Kurniasih, Try Indiastuti; Siska, Yulia (Program Studi PGMI, 2025)
The purpose of this study is to comprehensively explain the implementation of the Pancasila Student Profile Strengthening Project in Elementary Schools, including: school ecosystem readiness, strengthening project design, management procedures, assessment processing and reporting of results, evaluation and follow-up. The approach used in this study is mixed methods with divergent-convergent techniques. The subjects of this study were Elementary Schools in Lampung Province spread across various districts/cities. The data collection techniques used were: literature studies, observations, interviews, and questionnaires. The data analysis technique used was a combined parallel convergent method. The results of the study indicate that the implementation of the school-based Pancasila Student Profile Strengthening Project (P5) has been successfully implemented optimally; 2) the application of the Independent Curriculum in Learning is in the very good category; and 3) Internalization of the Pancasila Student Profile Strengthening Project has been carried out well in the Learning process.